CHILDREN'S ARTISTIC EXPERIENCE IN DRAWING EXPRESSIONS ON THE MENARA KUDUS - Mohammad Ridlo; Nur Fajrie; Mohammad Kanzunnudin; Hisbulloh Als Mustofa (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
The values embedded in the Menara Kudus culture in Indonesia emphasize the preservation and development of local traditions. One way children express their understanding of local culture is through artistic activities, particularly drawing. This study aims to narrate and measure children's artistic experiences in creating drawings themed on the Menara Kudus, using cultural evidence from its historical legacy as a learning resource. This study employed a mixed-methods sequential exploratory design. The initial qualitative phase involved interviews, observations, and documentation to explore children aged 9 to 12's artistic experiences. The subsequent quantitative phase applied descriptive statistics to support and measure the findings from the qualitative data. All qualitative data were analyzed using an interactive model. The results show that children produced drawings of the Menara Kudus based on their personal experiences and interests, with artworks displaying varying levels of precision, imagination, and creativity. The creative process was found to consist of three phases: pre-creation (encompassing both direct and indirect experiences), creation (encompassing tool preparation, technical mastery, time management, and effective communication), and post-creation (encompassing self-confidence and interpretation). The overall mean score for the artistic experience was 119.43, with mean scores of 22.57, 80.95, and 15.91 for the pre-creation, creation, and post-creation stages, respectively. The findings indicate that children's involvement in the visual arts themed on Menara Kudus is categorized as moderate. It is therefore recommended that children's skills in capturing the original form of objects be enhanced.